Hubungan Ilmu Psikologi dan Masalah-Masalah Hukum - Fattah Hanurawan (Fakultas Psikologi Universitas Negeri Malang, 2020)
Science is the arrangement of knowledge about a phenomenon obtained through scientific research methods whose truth has been agreed intersubjectively by a certain scientific community. The ultimate goal of science is to develop theories or paradigms that have functions: description, explanation, control, forecasting, and problem solving related to a phenomenon.